Novel Electrode Materials for Thin-Film Ultracapacitors : Comparison of Electrochemical Properties of Sol-Gel-Derived and Electrodeposited Manganese Dioxide - Pang, Suh Cem; Anderson, Marc A.; Chapmanb, Thomas W. (IOP Publishing Ltd., 2000)
Thin films of manganese dioxide were formed on nickel foils by electrodeposition and by both dip-coating and drop-coating with manganese dioxide suspensions (sols) and their subsequent gelation and calcination. The performance of these films as ultracapacitors was studied by cyclic voltammetry in the range 0.0-0.9 V (SCE) and by chronopotentiometry in unbuffered Na2SO4 solution. The cyclic voltammograms of ultrathin, dip-coated sol-gel-derived films indicated better capacitive behavior and gave differential specific capacitance values as high as 698 F/g compared to values half to two-thirds as great for the electrodeposited films. Multilayer drop-coated sol-gel films were prepared to attain film thicknesses comparable to the electrodeposited films, and these were found to provide charge-storage capacity as high as 15 mC/cm2, more than three times greater than that of the electrodeposited films. All films, except electrodeposited films that were not thermally cured, exhibited good cycling stability, losing not much more than 10% of capacity after 1500 cycles.